Comparison of Haglund Height and Angle in Persons with or without Insertional Achilles Tendinopathy - Shrestha, Praphulla; Chalise, Pralhad Kumar; Mishra, Anil Kumar (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Insertional Achilles tendinopathy (IAT) has been associated with Haglund deformity of the posterosuperior calcaneal tubercle. During surgical treatment of IAT, excision of the Haglund deformity is being performed as a routine, which adds morbidity. We wanted to find out if is that really necessary or not by comparing the Haglund height and angle between patients with IAT and the control group in our population. METHODS A cross-sectional study was performed on 68 patients in the department of Orthopaedics and Trauma from November 2023 to April 2024 after ethical approval (Ref no. 27-080/081). Measurement of Haglund height and angle was performed in the hospital PACS system. Other relevant angles and lines were also measured. Other important X-ray findings were also noted. RESULTS The mean Haglund height and Haglund angle in the IAT group were 3.97±1.65 mm and 7.35±3.15° respectively. In the control group, the mean Haglund height and Haglund angle were 2.99±1.33 mm and 5.38±2.49° respectively. Both Haglund height and angle were statistically significant when compared between groups. Also, the presence of posterior heel spur, calcification over the tendoachilles, and sclerosis of the posterior calcaneal tuberosity in x-ray was statistically significant in comparison between the two groups. CONCLUSION Our study concludes that Haglund deformity has a role in the pathogenesis of IAT, and its excision might be justified. The presence of posterior heel spur, calcification over the tendoachilles, and sclerosis of the posterior calcaneal tuberosity are key features in the x-ray of IAT.